2010
DOI: 10.1111/j.1745-3992.2010.00171.x
|View full text |Cite
|
Sign up to set email alerts
|

Can High School Achievement Tests Serve to Select College Students?

Abstract: Postsecondary schools have traditionally relied on admissions tests such as the SAT and ACT to select students. With high school achievement assessments in place in many states, it is important to ascertain whether scores from those exams can either supplement or supplant conventional admissions tests. In this study we examined whether the Arizona Instrument to Measure Standards (AIMS) high school tests could serve as a useful predictor of college performance. Stepwise regression analyses with a predetermined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 12 publications
0
18
2
Order By: Relevance
“…Linking state standards‐based assessments to postsecondary opportunities, such as college or vocational training, helps bridge the gap between secondary and postsecondary expectations for students. An added benefit from linking state standards‐based assessments with tangible outcomes such as course placement may be an increase in test validity, such as the increase reported by Cimetta et al () in their study of the Arizona standards‐based test before and after the test's establishment as a graduation requirement. Demonstrating the efficacy of state standards‐based assessments for specific college program placement provides an avenue for significant cost savings on the part of postsecondary institutions as well as increasing student motivation to perform well on the state standards‐based assessment.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Linking state standards‐based assessments to postsecondary opportunities, such as college or vocational training, helps bridge the gap between secondary and postsecondary expectations for students. An added benefit from linking state standards‐based assessments with tangible outcomes such as course placement may be an increase in test validity, such as the increase reported by Cimetta et al () in their study of the Arizona standards‐based test before and after the test's establishment as a graduation requirement. Demonstrating the efficacy of state standards‐based assessments for specific college program placement provides an avenue for significant cost savings on the part of postsecondary institutions as well as increasing student motivation to perform well on the state standards‐based assessment.…”
Section: Resultsmentioning
confidence: 99%
“…Wise and DeMars () found that low student motivation sizably increased student score variability which, in turn, is likely to mask relationships that may actually exist in the population. Cimetta et al () were in a unique position to observe the change in test score performance corresponding with tying the Arizona assessment to graduation requirements. Further, researcher in this area may benefit by focusing on states that associate student‐relevant outcomes with assessment performance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cimetta, D'Agostino, and Levin (2010) also cited several studies that have challenged the use of SAT scores as part of their research on the prospect of using state high school achievement tests (in Arizona) as a substitute for SAT scores. One of the biggest complaints regarding their use has been the claim that SAT questions are racially biased.…”
Section: Concerns Related To Using Cognitive Measuresmentioning
confidence: 99%